Activation of the Prostaglandin E2 receptor EP2 prevents house dust mite‐induced airway hyperresponsiveness and inflammation by restraining mast cells' activity. Issue 10 (15th September 2015) - Serra‐Pages, M.; Torres, R.; Plaza, J.; Herrerias, A.; Costa‐Farré, C.; Marco, A.; Jiménez, M.; Maurer, M.; Picado, C.; de Mora, F.
Summary: Background: Prostaglandin E2 (PGE2 ) has been proposed to exert antiasthmatic effects in patients, to prevent antigen‐induced airway pathology in murine models, and to inhibit mast cells (MC) activity in vitro . Objective: To assess in a murine model whether the protective effect of PGE2 may be a consequence of its ability to activate the E‐prostanoid (EP)2 receptor on airway MC. Methods: Either BALB/c or C57BL/6 mice were exposed intranasally (i.n.) to house dust mite (HDM) aeroallergens. Both strains were given PGE2 locally (0.3 mg/kg), but only BALB/c mice were administered butaprost (EP2 agonist: 0.3 mg/kg), or AH6809 (EP2 antagonist; 2.5 mg/kg) combined with the MC stabilizer sodium cromoglycate (SCG: 25 mg/kg). Airway hyperresponsiveness (AHR) and inflammation, along with lung MC activity, were evaluated. In addition, butaprost's effect was assessed in MC‐mediated passive cutaneous anaphylaxis (PCA) in mice challenged with 2, 4‐dinitrophenol (DNP). Results: Selective EP2 agonism attenuated aeroallergen‐caused AHR and inflammation in HDM‐exposed BALB/c mice, and this correlated with a reduced lung MC activity. Accordingly, the blockade of endogenous PGE2 by means of AH6809 worsened airway responsiveness in sensitive BALB/c mice, and such worsening was reversed by SCG. The relevance of MC to PGE2 ‐EP2 driven protection was further highlighted in MC‐dependent PCA, where butaprost fully prevented MC‐induced ear swelling. Unlike in BALB/c mice, PGE2 did not protect the airways of HDM‐sensitized C57BL/6 animals, a strain in which we showed MC to be irrelevant to aeroallergen‐driven AHR and inflammation. Conclusions & Clinical Relevance: The beneficial effect of both exogenous and endogenous PGE2 in aeroallergen‐sensitized mice may be attributable to the activation of the EP2 receptor, which in turn acts as a restrainer of airway MC activity. This opens a path towards the identification of therapeutic targets against asthma along the 'EP2 ‐MC‐airway' axis.